Susceptibility of Campylobacter Strains to Selected Natural Products and Frontline Antibiotics - Gahamanyi, Noel; Song, Dae-Geun; Cha, Kwang Hyun; Yoon, Kye-Yoon; Mboera, Leonard E. G.; Matee, Mecky I.; Mutangana, Dieudonne; Amachawadi, Raghavendra G.; Komba, Erick V. G.; Pan, Cheol-Ho (MDPI, 2020)
Campylobacter species have developed resistance to existing antibiotics. The development of alternative therapies is, therefore, a necessity. This study evaluates the susceptibility of Campylobacter strains to selected natural products (NPs) and frontline antibiotics. Two C. jejuni strains (ATCC(R) 33560(TM) and MT947450) and two C. coli strains (ATCC(R) 33559(TM) and MT947451) were used. The antimicrobial potential of the NPs, including plant extracts, essential oils, and pure phytochemicals, was evaluated by broth microdilution. The growth was measured by spectrophotometry and iodonitrotetrazolium chloride. Antibiotic resistance genes (tet(O) and gyrA) were characterized at the molecular level. The minimum inhibitory concentrations (MICs) and the minimum bactericidal concentrations (MBCs) ranged from 25 to 1600 mu g/mL. Cinnamon oil, (E)-Cinnamaldehyde, clove oil, eugenol, and baicalein had the lowest MIC and MBC values (25-100 mu g/mL). MT947450 and MT947451 were sensitive to erythromycin and gentamicin but resistant to quinolones and tetracycline. Mutations in gyrA and tet(O) genes from resistant strains were confirmed by sequencing. The findings show that NPs are effective against drug-sensitive and drug-resistant Campylobacter strains. The resistance to antibiotics was confirmed at phenotypic and genotypic levels. This merits further studies to decipher the action mechanisms and synergistic activities of NPs.
Keywords: ESSENTIAL OILS; STAPHYLOCOCCUS-AUREUS; FLUOROQUINOLONE RESISTANCE; SOPHORA-FLAVESCENS; ANTIMICROBIAL SUSCEPTIBILITIES; ANTIBACTERIAL PROPERTIES; BIOFILM FORMATION; MEDICINAL-PLANTS; GYRA GENE; JEJUNI